Early allelopathic input and later nutrient addition mediated by litter decomposition of invasive Solidago canadensis affect native plant and facilitate its invasion - Sun, Jianfan; Fu, Yundi; Hu, Wenjie; Bo, Yanwen; Nawaz, Mohsin; Javed, Qaiser; Khattak, Wajid Ali; Akbar, Rasheed; Xiaoyan, Wang; Liu, Wei; Du, Daolin (Frontiers in Plant Science, 2024)
Litter decomposition is essential for nutrient and chemical cycling in terrestrial ecosystems. Past research on in-situ litter decomposition has often underestimated its impact on soil nutrient dynamics and allelopathy. To address this gap, we conducted a comprehensive study involving both field and greenhouse experiments to examine the decomposition and allelopathic effects of the invasive Solidago canadensis L. in comparison with the native Phalaris arundinacea L. In the field, we conducted a six-month litter bag experiment using leaf litter from S. canadensis and P. arundinacea across three community types: invasive, native, and mixed. Seed germination tests were also performed to investigate the allelopathic effects of decomposing litter. In the greenhouse, a pot experiment with lettuce as a bioindicator examined the allelochemical inputs from litter decomposition over various time intervals (0, 30, 60, 120, and 180 days). Subsequently, a soil-plant feedback experiment was carried out to further evaluate the effects of decomposing litter on soil biochemistry and plant dynamics. The findings of this study revealed that S. canadensis litter decomposed more rapidly and exhibited greater nitrogen (N) remaining mass compared to P. arundinacea in both mono and mixed communities. After 180 days, litter mass remaining was 36% for S. canadensis and 43% for P. arundinacea when grown separately, and 32% for S. canadensis and 44% for P. arundinacea in mixed communities. At the invasive site, soil ammonia and nitrate for S. canadensis increased gradually, reaching 0.89 mg/kg and 14.93 mg/kg by day 120, compared to the native site with P. arundinacea. Soil organic carbon for S. canadensis at the invasive site also rose from 10.6 mg/kg on day 0 to 15.82 mg/kg on day 120, showing a higher increase than at the native site with P. arundinacea. During the initial decomposition stages, all litters released almost all of their allelochemicals. However, at later stages, litters continued to input nutrients into the soil. Notably, litter-mediated plant-soil feedback facilitated the invasion of S. canadensis. In conclusion, our study highlights the significance of litter decomposition as a driver of transforming soil biochemistry, influencing the success of invasive S. canadensis.